脳卒中片麻痺患者の車椅子移乗動作に関する分析 - 髙栁 智子; 川西 千恵美; 西田 直子; 田澤 賢次 (日本看護研究学会雑誌, 2001)
The "non-affected-side approach" is a widely used principle of transfer activities for hemiplegic patients； the object of transfer is set on the non-affected side. On the other hand, the "affected- side approach" sets the object on the patient's affected side. We conducted motion analysis using the non-affected-side approach, and the affected-side approach of transfer in order to investigate the effects on patients.The subjects consisted of 6 patients who were hemiplegic after stroke. The lateral shifts of center of gravity on the affected-side approach were significantly (p<0.05) larger than those on the non-affected-side approach. The lengths of the anterior-posterior locus of the center of gravity on the non-affected-side approach were significantly (p<0.05) longer than those on the affected-side approach. Median times for transferring on the non-affected-side approach and the affected-side approach in 2 patients whose affected legs were Brunnstrom Stage II were 8.8 sec and 12.3 sec, and they had shorter times for transferring and felt more comfortable using the non-affected-side approach. In four patients whose affected legs were Brunnstrom Stage III, there was no significant difference in transfer times between the non-affected-side approach, and they also felt more comfortable using the affected-side approach. These findings suggest that, with some degree of support, the affected-side approach for hemiplegia is safe and comfortable for patients. 脳卒中後の片麻痺患者6名を被験者に，目的物を健側に置く健側配置と患側に置く患側配置の移乗動作の動作経済性および安定性について，三次元動作解析装置を用いて比較した｡ 動作経済性は，動作時間と重心の変位を，安定性は，重心の軌跡および目視による動作観察，主観的情報を評価した｡ 1) 動作経済性では，健側配置，患側配置における左右方向の重心変位の中央値は，それぞれ35.0cm，52.3cmと患側配置で有意に大きかった｡ 前後方向の重心の軌跡長の中央値は，それぞれ130.82cm，120.17cmと健側配置で有意に長かった｡ また，下肢 Brunnstrom StageⅡの被験者における健側配置，患側配置での動作時間の中央値は，それぞれ8.8秒，12.3秒と健側配置で有意に短かったが，下肢 Brunnstrom StageⅢの被験者では，有意差は認められなかった｡ 2) 安定性では，下肢 Brunnstrom StageⅡの被験者は，重心の軌跡をみると，患側配置での移乗においてバランスを崩しており，動作観察でも患側の膝折れがみられた｡ 下肢 Brunnstrom StageⅢの被験者では，どちらの配置でも移乗動作は安定していた｡ 　これらより，患側下肢に支持性がある者は，患側配置でも安全・安楽であることが示唆された｡